The research history of the miraculous birth motif of folklore (Eurasian Journal of Philology Science and Education, 2020)
The article explores the research history of the miraculous birth motif. It is reported that many researchers have applied this issue. Historically, the historical roots of the miraculous birth motif have beenlinked to the first humans. The miraclouse birth motif found in epic folklore is the transformation that isrelated to these concepts and transformed. The miraculous conception of life is divided into two parts:Miraculous fertilization. 2. Miraclous birth. The motive of the wonderful birth of the hero, as well as thewonderful and immaculate conception, are part of the system of motives about the origin of the hero inepic tradition. And the motive of a wonderful birth in turn consists of story-motivated unity, which serveto reveal certain features of epic heroes. These motives are also dominated by mythological representations of a people. In Azerbaijani folklore, this plot is considered the most common, as many fairy talesand epos include these story-motivated eelements. Motif of wonderful conception and wonderful birthinclude elements such as – conception from plants, wood (apple, barley,), etc., conception from totem,created from dough, clay, etc. This problem was at all times the focus of researchers of oral folk literature.